2016
DOI: 10.1515/jccm-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Sugammadex: An Update

Abstract: The purpose of this update is to provide recent knowledge and debates regarding the use of sugammadex in the fields of anesthesia and critical care. The review is not intended to provide a comprehensive description of sugammadex and its clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
0
8
0
1
Order By: Relevance
“…Sugammadex, a selective relaxant‐binding agent, was specifically developed for rapid reversal of rocuronium‐induced NMB 22 . By selectively binding to NMB agents, sugammadex inactivates free NMB agents in the plasma, resulting in a large concentration gradient of NMB agent molecules between the neuromuscular junction and the plasma, leading to decreased NMB agents at the neuromuscular junction end plate 23 . This mechanism allows neuromuscular transmission to resume in a short period of time, making it a more popular drug for IONM compared with other reversal agents 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugammadex, a selective relaxant‐binding agent, was specifically developed for rapid reversal of rocuronium‐induced NMB 22 . By selectively binding to NMB agents, sugammadex inactivates free NMB agents in the plasma, resulting in a large concentration gradient of NMB agent molecules between the neuromuscular junction and the plasma, leading to decreased NMB agents at the neuromuscular junction end plate 23 . This mechanism allows neuromuscular transmission to resume in a short period of time, making it a more popular drug for IONM compared with other reversal agents 24 .…”
Section: Discussionmentioning
confidence: 99%
“…While NMB reversal is crucial for IONM, maintaining adequate muscle relaxation during surgery is even more important. Because sugammadex allows faster return of muscle activity, bucking and movement during surgery are the most frequently reported adverse effects associated its use 23 . In fact, studies have reported that 20–35% of patients administered sugammadex (2 mg/kg) as a reversal agent for IONM had bucking events during surgery 7,21 .…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be noted that the CICO scenario is often multifactorial and reversing NMB agents may not always be a solution. 10 In these cases, emergent tracheostomy may be required, and, therefore, the operating room would be an ideal environment. In our hospital, an otolaryngologist is not always present in cases when difficult intubation is anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Our survey asked participants whether or not their hospitals had access to sugammadex and whether or not they had policies for the use of sugammadex. Based on current literature, we identified eight clinical scenarios in which sugammadex may be indicated for use . Similarly, we identified four patient populations where sugammadex may be specifically indicated.…”
Section: Methodsmentioning
confidence: 99%